Happy Voters - Federica Liberini; Michela Redoano; Eugenio Proto (Institute for the Study of Labor (IZA), 2014)
Motivated by recent interest and initiatives taken by several governments and international organizations to come up with indicators of well-being to inform policy makers, we test if subjective well-being measures (SWB) can be employed to study voting behaviour. Controlling for financial and economic circumstances, we find that when citizens are more satisfied with their life, they are also more likely to cast their vote in favor of the ruling party. We address the possible concern of reverse causality in the relationship between SWB and political support by (i) analysing the political behaviour of a sample of ideologically neutral voters, and (ii) by identifying the effect of SWB on voting intentions in individuals' response to an exogenous shock of (un)happiness (i.e. the death of husband or wife). We conclude that SWB explains voting decisions, even when the event affecting well-being is beyond government's control.
Keywords: H11; H2; H77; H87; D7; N12; 330; subjective well-being; happiness; retrospective voting